Tetanus Toxin Blocks the Exocytosis of Synaptic Vesicles Clustered at Synapses But Not of Synaptic Vesicles in Isolated Axons - Verderio, Claudia (J Neurosci, 1999)
Recycling synaptic vesicles are already present in isolated axons of developing neurons (Matteoli et al., 1992; Zakharenko et al., 1999). This vesicle recycling is distinct from the vesicular traffic implicated in axon outgrowth. Formation of synaptic contacts coincides with a clustering of synaptic vesicles at the contact site and with a downregulation of their basal rate of exo-endocytosis (Kraszewski et al., 1995; Coco et al., 1998) We report here that tetanus toxin-mediated cleavage of synaptobrevin/vesicle-associated membrane protein (VAMP2), previously shown not to affect axon outgrowth, also does not inhibit synaptic vesicle exocytosis in isolated axons, despite its potent blocking effect on their exocytosis at synapses. This differential effect of tetanus toxin could be seen even on different branches of a same neuron. In contrast, botulinum toxins A and E [which cleave synaptosome-associated protein of 25 kDa. (SNAP-25)] and F (which cleaves synaptobrevin/VAMP1 and 2) blocked synaptic vesicle exocytosis both in isolated axons and at synapses, strongly suggesting that this process is dependent on “classical” synaptic SNAP receptor (SNARE) complexes both before and after synaptogenesis. A tetanus toxin-resistant form of synaptic vesicle recycling, which proceeds in the absence of external stimuli and is sensitive to botulinum toxin F, E, and A, persists at mature synapses. These data suggest the involvement of a tetanus toxin-resistant, but botulinum F-sensitive, isoform of synaptobrevin/VAMP in synaptic vesicle exocytosis before synapse formation and the partial persistence of this form of exocytosis at mature synaptic contacts.